Biomechanical differences before and after arthroscopic partial meniscectomy in patients with semilunar and discoid lateral meniscus injury - Li, Yaqiang (Am J Transl Res, 2020)
The purpose of the current study was to investigate the differences in knee kinematics and kinetics in patients with semilunar lateral meniscus (SLM) and discoid lateral meniscus (DLM) injuries before and after arthroscopic partial meniscectomy during level walking. Fifteen healthy volunteers (control group), thirteen patients with SLM injury (SLM group) and nine patients with DLM injury (DLM group) were enrolled in our study. Gait analyses were performed pre- and post-operatively during level walking at a self-selected walking speed. Our results showed that compared to the control group before surgery, the SLM and DLM groups showed significantly lower walking speed, shorter stride length, lower maximum knee flexion during stance phase and swing phase, lower first peak knee flexion moment, and smaller adduction-abduction range of motion (ROM) during the gait cycle. Compared to the control group, only the DLM group showed significantly decreased flexion-extension ROM and maximum abduction angle. The first peak knee adduction moment was lower in the SLM group than in the control group. Significant difference was observed in first peak knee flexion moment between SLM and DLM groups. After surgery, there were no significant differences in gait spatiotemporal parameters, knee kinematics, and kinetics between the three groups, indicating that meniscectomy is an effective treatment for both types of injury. By using three-dimensional gait analysis, the current results revealed that lateral meniscus types influence gait patterns after injury, which may further impact clinical treatment choice and long-term prognosis.